Leptin reduction after endurance races differing in duration and energy expenditure - Zaccaria, M.; Ermolao, A.; Roi, G. S.; Englaro, P.; Tegon, G.; Varnier, M. (European Journal of Applied Physiology, 2002)
Serum leptin concentrations are reduced in the presence of a negative energy balance. It has been demonstrated, however, that strenuous and prolonged exercise, which induces a marked negative energy balance, is not always followed by a reduction in serum leptin levels. We therefore analysed serum leptin concentrations before and after three endurance races, which differed in duration and energy expenditure (EE), with the aim of clarifying the relationship between the level of EE and the reduction in leptin levels. Forty-five males participated in one of three competitive endurance races, a half-marathon run [21.097 km, estimated EE 1,400 kcal (5,852 kJ)], a ski-alpinism race [about 45 km, estimated EE 5,000 kcal (20,900 kJ)], and an ultramarathon race [100 km, estimated EE 7,000 kcal (29,269 kJ)]. Blood samples for analysis of serum leptin, and plasma free fatty acids (FFA) were collected before and after the races. Pre-race leptin values were significantly correlated with both body mass index and body fat mass (r=0.672 and r=0.699, respectively; P<0.0001). After exercise, serum leptin levels decreased significantly in the ultramarathon [from 4.15 (0.63) µg/l to 1.01 (0.15) µg/l; P<0.001] and in the ski-alpinism race [from 1.10 (0.28) µg/l to 0.62 (0.15) µg/l; P<0.01], but not in the half-marathon [from 1.38 (0.40) µg/l to 1.20 (0.36) µg/l]. Plasma FFA were found to have significantly increased in all three of the races, showing a negative correlation with the percent reduction in leptin (r=0.369, P<0.02). Our data indicate that only a prolonged endurance exercise involving a high EE can induce a marked reduction in circulating serum leptin levels.